Performance Measure Properties and Delegation - Moers, Frank (The Accounting Review, 2006)
In this paper, I extend the organizational design literature by examining how the delegation choice is affected by the ability to resolve the incentive problem caused by this delegation. Based on the seminal papers by Grossman and Hart (1986) and Holmstrom and Milgrom (1994), I argue that the ability to resolve the incentive problem depends on the contractibility of financial performance measures versus non-financial performance measures, where the contractibility depends on the performance measure properties sensitivity, precision, and verifiability. The empirical results show that, if financial performance measures are good (poor) incentive measures, i.e., high (low) on sensitivity, precision, and verifiability, then using these measures for incentive purposes increases (decreases) delegation. Overall, the results are consistent with the argument that firms design their organizational structure around the quality of contractible performance measures.